Evaluation of Nutritional Services for the Inpatients at X Hospital Yogyakarta - Rina Adhiyati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Nutritional services management contributes to the acceleration of healing process, health maintenance and nutritional status improvement. Poor nutritional service management leads to a high risk of patients’ health degradation, and it even can lead to death. This study aims to evaluate the implementation of three aspects of nutritional service management, namely human resources, method, and equipment in the third-class ward of X Hospital. The methods used in the research were mix research methods which involved descriptive observational design. Data collection was conducted in a cross-sectional manner. Respondents selected included 30 nurses and 2 nutritionists while informants consisted of 5 nurses and 2 nutritionists. The data collection used questionnaires, checklists and interview guides. Observation of patients’ medical records was done retrospectively in 3 months, involving 30 files. The quantitative analysis used descriptive-inferential statistics and correlation test. The qualitative data were analysed on the basis of codes of themes and sub themes. The results of the study found that the management of human resources in regard to nurses and nutritionists was not yet good, management of nutritional service management performed by the nurses was good but was in contrast to the management performed by the nutritionists, which was not good, and equipment management was good. To improve the performance of nutritional services management, it is necessary to adjust the management in accordance with the existing rules and guidelines, implementation of socialization, supervision, monitoring and evaluation on a regular basis.